A Cross-Jurisdictional Exploration of Inadvertent Negligence in Legal Theory and Practice - Mustafa, Cecep (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
This paper explores the complexities of criminal liability for inadvertent negligence through a comparative and interdisciplinary approach. While civil law jurisdictions, such as Germany, embrace a broad scope for criminal negligence, common law systems, including those in the United States and the United Kingdom, and typically restrict criminal liability to more severe forms of negligence. By integrating legal theory with philosophical and psychological perspectives, this study examines the moral and cognitive dimensions of negligence. It proposes a framework for a more just and effective legal system. The findings highlight significant disparities between legal systems and provide recommendations for harmonizing definitions, enhancing judicial training, increasing public awareness, and promoting international dialogue. This research contributes novel insights into the application of negligence laws and advocates for a balanced approach to criminal liability.